Do Multinationals Influence Labor Standards? A Close Look at US Outward FDI - Konstantin M. Wacker; Krishna Chaitanya Vadlamannati (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
This paper investigates the effects of multinational corporations on labor standards. We argue that the previous literature has failed to distinguish the different motives that encourage fi rms to become multinational. Therefore, we build a stylized model of segmented labor markets with equilibrium unemployment where parts of the labor force are willing to accept reductions in their labor standards to attract job-creating horizontal foreign direct investment. By disentangling US FDI data for 34 advanced host countries throughout the period 1997 to 2002 into vertically and horizontally motivated FDI, we show that this disaggregation provides much more signifi cant results. Concretely, we find a statistically signifi cant and economically considerable negative impact of horizontal US FDI on labor right practices in industrialized host countries by using a static OLS model and qualitatively similar results with dynamic GMM estimation. Our results do not imply that this effect leads to a decrease in welfare in the host economy but that in the welfare optimization process employment, income and job-quality serve as substitutes with an elasticity positively depending on equilibrium unemployment.
Keywords: F2; J81; C23; M14; 330; Multinationals; FDI; Labor Rights; Labor Markets